1993
DOI: 10.1002/oms.1210281018
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of ethane‐1,2‐diol radical cations: Processes involving dipole‐catalyzed proton shifts and charge transfer

Abstract: Rearrangement and dissociation processes of solitary ethane-1,Zdiol radical cations were investigated by ab in& MO calculations, executed at the SDCI//RHF/DZP level of theory, including Pople-type size-consistency corrections. In order to obtain an accurate description of the chemistry involved, part of the potential energy surface was investigated by using the multi-reference CI method and also by using the valence bond (VB) method followed by SDCI calculations using the natural orbitals of the VB wavefunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Instead, we found that the initial structure for 4 transformed without activation to a hydrogen-bonded hydrate of the anti -vinyl alcohol radical cation, 19 , 27.2 kcal/mol lower in energy. Frequency analysis confirms that 19 is a local minimum on the C 2 H 6 O 2 ⎤•+ PES. 10a,d The transformation involves the H 2 O group on the right-hand carbon atom, C 2 , moving far to the left of C 1 without the formation of the protonated gem -diol radical structure 6 as an intermediate. In the optimized structure, C 2 ···O 4 = 4.540 Å and C 1 ···O 4 = 3.144 Å.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Instead, we found that the initial structure for 4 transformed without activation to a hydrogen-bonded hydrate of the anti -vinyl alcohol radical cation, 19 , 27.2 kcal/mol lower in energy. Frequency analysis confirms that 19 is a local minimum on the C 2 H 6 O 2 ⎤•+ PES. 10a,d The transformation involves the H 2 O group on the right-hand carbon atom, C 2 , moving far to the left of C 1 without the formation of the protonated gem -diol radical structure 6 as an intermediate. In the optimized structure, C 2 ···O 4 = 4.540 Å and C 1 ···O 4 = 3.144 Å.…”
Section: Resultsmentioning
confidence: 75%
“…At level B , 20 is found to be 15.8 kcal/mol higher in energy than 19 , of which 2.3 kcal/mol can be attributed to the difference in stability between the syn - and anti -rotamers of the vinyl alcohol radical cation; see Table 21S. The hydrogen-bonded hydrate of the syn -vinyl alcohol radical cation, 21 , which results from a 180° rotation of the H 2 OHO− grouping about the C−O bond or inversion of the HO group with respect to the C−O bond in the anti -structure, 10a,d is considerably more stableonly 1.8 kcal/mol higher in energy than 19 at level A ; see Table 21S. …”
Section: Resultsmentioning
confidence: 99%
“…However, the C−C bond in the UMP2/6-31G** optimized structure is slightly shorter (1.775 Å). The presence of a long C−C bond in an organic radical cation is not unprecedented: the ions CH 3 CH 2 OH •+ and HOCH 2 CH 2 OH •+ have been calculated to have structures with remarkably long one-electron C−C bonds (CH 3 CH 2 OH •+ , 2.013 Å at the UHF/4-31G level; 40a,b HOCH 2 CH 2 OH •+ , 2.01 Å at the RHF/DZP level 40c ). The results obtained in the above calculations, especially the long C−C bond in 1‘‘ , as well as the location of the greatest positive charge at the hydroxyl hydrogen in this ion (Figure ), support the proposal that the entering nucleophile initially forms a hydrogen bond with the hydroxyl hydrogen, as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…17 This ion was suggested to undergo a hydrogen atom shift to yield another hydrogen-bridged intermediate, (CH 3 ) 2 -O‚‚‚H‚‚‚OdCH •+ (3), which decomposes by expulsion of CHO • . A similar mechanism was proposed 19 for the loss of CHO • from the molecular ion of ethylene glycol, but this mechanism was later proved to be incorrect through labeling experiments. 20,21 The role of hydrogen-bridged intermediates in the dissociation of CH 3 OCH 2 CH 2 OH •+ was reinvestigated 20,21 by using differently deuterated analogues of CH 3 OCH 2 CH 2 OH.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation